Human enterovirus 71 subgenotype B3 lacks coxsackievirus A16-like neurovirulence in mice infection - Chan, Y.F.; AbuBakar, Sazaly (2005)
Background: At least three different EV-71 subgenotypes were identified from an outbreak in Malaysia in 1998. The subgenotypes C2 and B4 were associated with the severe and fatal infections, whereas the B3 virus was associated with mild to subclinical infections. The B3 virus genome sequences had â¥85 similarity at the 3' end to CV-A16. This offers opportunities to examine if there are characteristic similarities and differences in virulence between CV-A16, EV-71 B3 and EV- 71 B4 and to determine if the presence of the CV-A16-liked genes in EV-71 B3 would also confer the virus with a CV-A16-liked neurovirulence in mice model infection. Results: Analysis of human enterovirus 71 (EV-71) subgenotype B3 genome sequences revealed that the 3D RNA polymerase and domain Z of the 3'-untranslating region RNA secondary structure had high similarity to CV-A16. Intracerebral inoculation of one-day old mice with the virus resulted in 16 of the mice showing swollen hind limbs and significantly lower weight gain in comparison to EV-71 B4-infected mice. None of the mice presented with hind leg paralysis typical in all the CV-A16 infected mice. CV-A16 genome sequences were amplified from the CV-A16- infected mice brain but no amplification was obtained from all the EV-71-inoculated mice suggesting that no replication had taken place in the suckling mice brain. The findings presented here suggest that EV-71 B3 viruses had CV-A16-liked non- structural gene features at the 3'-end of the genome. Their presence could have affected virulence by affecting the mice general health but was insufficient to confer the EV-71 B3 virus a CV-A16- liked neurovirulence in mice model infection.